Professional Training of Future Teachers of Physical Culture for Animation Leisure Activities - Holenkov, Anton (Educational Challenges, 2024)
The purpose of the study is to determine the need for professional competencies development for future teachers of physical culture in the field of animation leisure activities, taking into account modern educational requirements and trends. The research methodology for preparing future teachers of physical education for animation leisure activities includes several key methods and approaches. One of the main methods is the analysis of scientific literature, including the study of existing research papers, articles, and monographs related to the professional training of future teachers of physical education for animation activities. To achieve the research objectives, it is necessary to define and analyze the concepts “professional training”, “animation leisure activities”, “competence”, and other important terms. This methodology allows a comprehensive study of the process of preparing future physical education teachers for animation leisure activities. Results. It has been found that animation leisure activities play a significant role in the professional training of future physical education teachers, as they contribute to the development of professional competencies, creativity, and communication skills. This concept encompasses various activities and actions that help students not only master the methods of organizing leisure activities but also develop the ability to engage others in an active and healthy lifestyle. Conclusions. Animation as an educational component can make a school lesson more engaging through various methods, forms, and means. Animation can be fully applied as a creative learning activity that develops learners’ potential while also encouraging them to challenge current social issues. Animation is viewed not only within the context of leisure but also as an opportunity to be applied in the educational practice of modern education.